Effects of Selenium Yeast on Oxidative Stress, Growth Inhibition, and Apoptosis in Human Breast Cancer Cells - Guo, Chih-Hung; Hsia, Simon; Shih, Min-Yi; Hsieh, Fang-Chin; Chen, Pei-Chung (My University, 2015)
Recent evidence suggests that selenium (Se) yeast may exhibit potential anti-cancer properties; whereas the precise mechanisms remain unknown. The present study was aimed at evaluating the effects of Se yeast on oxidative stress, growth inhibition, and apoptosis in human breast cancer cells. Treatments of ER-positive MCF-7 and triple-negative MDA-MB-231 cells with Se yeast (100, 750, and 1500 ng Se/mL), methylseleninic acid (MSA, 1500 ng Se/mL), or methylselenocysteine (MSC, 1500 ng Se/mL) at a time course experiment (at 24, 48, 72, and 96 h) were analyzed. Se yeast inhibited the growth of these cancer cells in a dose- and time-dependent manner. Compared with the same level of MSA, cancer cells exposure to Se yeast exhibited a lower growth-inhibitory response. The latter has also lower superoxide production and reduced antioxidant enzyme activities. Furthermore, MSA (1500 ng Se/mL)-exposed non-tumorigenic human mammary epithelial cells (HMEC) have a significant growth inhibitory effect, but not Se yeast and MSC. Compared with MSA, Se yeast resulted in a greater increase in the early apoptosis in MCF-7 cells as well as a lower proportion of early and late apoptosis in MDA-MB-231 cells. In addition, nuclear morphological changes and loss of mitochondrial membrane potential were observed. In conclusion, a dose of 100 to 1500 ng Se/mL of Se yeast can increase oxidative stress, and stimulate growth inhibitory effects and apoptosis induction in breast cancer cell lines, but does not affect non-tumorigenic cells.
Keywords: Selenium Yeast; Oxidative Stress; Apoptosis; Breast Cancer Cells